International Long-distance Commuting in the Resources Sector: Why Do Resource Workers Choose to Work in Australia but Live in Bali - Hoath, A.; Davies, Amanda (Springer, 2016)
Growth during the recent boom in the number of Australian resources industry fly-in/fly-out (FIFO) workers choosing to work on Australian-based mines or oil and gas sites, but live outside of Australia, has attracted considerable media and public attention. However, until now, the motivations for entering into transnational FIFO arrangements from a foreign base, and the specific challenges and rewards that such decisions bring for both workers and their differently positioned spouses, have received little scholarly attention. This chapter explores the case of expatriate FIFO resources sector workers who are undertaking transnational commutes from Bali to worksites in Australia. It considers why Bali has emerged as their preferred home location. The chapter argues that in electing to engage in transnational FIFO arrangements, many are thinking strategically about balancing their income earning potential and conditions of employment while maximizing lifestyle possibilities for themselves and their families. This involves negotiating a complex, of often, contradictory priorities and expectations.